2013
DOI: 10.1055/s-0033-1343079
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Chronic Static Scapholunate Dissociation Post Soft Tissue Reconstruction

Abstract: The purpose of this study was to examine the radiographic outcomes of dorsal intercarpal ligament capsulodesis (DILC), documenting the time to carpal collapse postoperatively. From January 2008 to January 2011, 12 patients were identified with chronic scapholunate (SL) dissociation. The average follow-up period was 15.8 months.Paired t-tests were used preoperatively, one month after pin removal, and at final followup to determine significance in radiographic outcomes. The Disabilities of the Arm, Shoulder, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Deshmukh et al reported mean wrist extension/flexion of 38°/40°after performing 44 capsulodesis procedures for chronic SL instability, but was limited by a disproportionate number of worker compensation claims and prolonged injury-to-treatment time averaging 52 months [8]. Similar results were reported by Yang et al after review of 12 wrists with chronic stable SL instability undergoing capsulodesis [26]. The latter study additionally noted almost immediate radiographic deterioration of the SL gap within 1 month, which is consistent with the poorer radiographic findings for capsulodesis in our present review.…”
Section: Discussionsupporting
confidence: 55%
“…Deshmukh et al reported mean wrist extension/flexion of 38°/40°after performing 44 capsulodesis procedures for chronic SL instability, but was limited by a disproportionate number of worker compensation claims and prolonged injury-to-treatment time averaging 52 months [8]. Similar results were reported by Yang et al after review of 12 wrists with chronic stable SL instability undergoing capsulodesis [26]. The latter study additionally noted almost immediate radiographic deterioration of the SL gap within 1 month, which is consistent with the poorer radiographic findings for capsulodesis in our present review.…”
Section: Discussionsupporting
confidence: 55%
“…Long-term studies of patients undergoing SL repair or reconstruction after chronic SLIL injury have shown a pattern of radiographic deterioration with time. [6][7][8][9][10] We were unable to identify any studies that correlated radiographic findings and pain/functional outcome scores. 7 Finding an association between these parameters would be important for guiding preoperative planning and establishing surgical goals.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrate radiographic, objective, and patient-reported outcomes (PROs) after SLIL reconstruction surgeries. [6][7][8][9][10] While these studies generally demonstrate improvement in functional outcomes and pain, the striking feature in their results is long-term radiographic deterioration. It is also notable that no correlation has been demonstrated between radiographic measurements and PROs.…”
mentioning
confidence: 99%